Study of starch degrading bacteria from kitchen waste soil in the production of amylase by using paddy straw - M.G. Tyagi, N.H. Shah, N.A.J.A. Justin, B.I. Santhose, K. Sathiyaseelan, S.V. Raj, A.K. Raja, A.B. Vimalanathan (Recent Research in Science and Technology, 2009)
The starch degrading amylolytic enzymes are of crucial importance in biotechnology industries with huge application in food, fermentation, textile and paper production. They are universally distribution in bacteria and fungus. Present study aimed at production of pure form of Î±-amylase from kitchen waste soil with optimization of raw material such as carbon and nitrogen source of the culture media for it. Objective: To evaluate the kitchen waste soil for production of Î±-amylase with optimization of carbon and nitrogen source required for culture media. Method: The starch degrading bacteria was isolated from the kitchen waste soil environment and was used for production of Î±-amylase through submerged. The paddy straw extract was shown the best source of carbon and potassium nitrate as the best source of nitrogen with optimum pH 7.0 and temperature of 30ÂºC. The fermentor parameters were set with the agitator at speed 200rpm with 100% dissolved O2 at fixed temperature and pH. After completion of the fermentation process, the activity of the enzyme was checked by the DNS method. Results: Enzyme produced and purified by this method, was found to have an enzymatic activity of 0.51 mg/ml after column chromatography by nanodrop spectrophotometer and coincide with standard in SDS-PAGE. Here, we have shown the cheap method of commercial production of economically valuable amylase by utilizing paddy straw.